2022
DOI: 10.3389/fgene.2022.875694
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Analysis in Neurological Wilson’s Disease Patients With Neurological Worsening Following Chelator Therapy

Abstract: Objectives: None of the previous studies have focused on the genetic effect on neurological worsening in neurological Wilson’s disease (WD) patients following chelator therapy. We aimed to evaluate the clinical and genetic role in the occurrence of neurological worsening.Methods: We retrospectively reviewed the medical records of neurological WD patients who received initial chelator therapy and genetic test. Clinical, laboratory, and genetic data were collected. The genotype was classified into two types: 1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In our study, we found only statistically significant trend towards longer disease latency (time from symptoms onset to treatment introduction in WD) as a predictor of neurological deterioration. Previous study by Litwin et al [14] did not find such effect, and other studies evaluating predictors of early neurological deterioration did not include this parameter in analysis [24,31,32]. Lack of positive results in this topic may be due to possible problems with definition of age at symptoms onset, which mainly depends on treating physicians' decision and patients' data availability [33,34].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In our study, we found only statistically significant trend towards longer disease latency (time from symptoms onset to treatment introduction in WD) as a predictor of neurological deterioration. Previous study by Litwin et al [14] did not find such effect, and other studies evaluating predictors of early neurological deterioration did not include this parameter in analysis [24,31,32]. Lack of positive results in this topic may be due to possible problems with definition of age at symptoms onset, which mainly depends on treating physicians' decision and patients' data availability [33,34].…”
Section: Discussionmentioning
confidence: 98%
“…At baseline, the mean acute toxicity score was non-significantly greater in patients that worsened after 6 months. Because the deterioration was observed only in patients with neurological symptoms at diagnosis, and only initial sNfL concentrations predicted the neurological deterioration in this subgroup, higher UWDRS and brain MRI scores reflected a greater severity of neurological disease [ 14 , 23 , 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations